Influence of the pile stiffness on the ground slab behaviour - Urbonas, Kęstutis; Sližytė, Danutė; Mackevičius, Rimantas (Journal of Civil Engineering and Management, 2016)
Just as other structural elements, ground slabs are an important unit of a building. It is especially true in the case of buildings, such as logistic centres, for which the primary purpose is storage of various goods. In this kind of buildings, floor slabs usually have high loads. For buildings where truck lifts are used, there are special requirements for flatness tolerance across and along the driving track of truck lifts. Therefore, the floor settlement differences in selected distances are limited. In localities where the soils under the floor slab are weak, they should be replaced or compacted. If these solutions are not possible or economically inappropriate, the slabs have to be supported on piles that must be based on strong deep soils. During the design process, it is very important to assign a proper value of rigidity of the piles. Pile stiffness has an enormous influence on the settlement of the slab as well as on the reinforcement intensity of the slab or even on the slab thickness. This paper presents the methodology for the evaluation of pile stiffness. In addition, it provides recommendations for the calculation of the floor slab on the piles. Calculations and obtained results confirmed the importance of certain design stages.